Pengembangan Media Video Animasi Berbantuan Capcut pada Pembelajaran IPS Materi Indahnya Keragaman di Negeriku Kelas IV Sekolah Dasar - Priskalia Putri; Muhamad Idris; David Budi Irawan (Universitas Pahlawan Tuanku Tambusai, 2023)
The development of animated video as media intends to assess the viability of students responses to the animated video in